Está en la página 1de 7

Problemas del 6-22 al 6-35 2 2

x 3 + y 3 =1
6-22
4 x 2 +9 y 2=36 1 1
2 3 2 3
x + y =0
dy 3 3
8 x+18 y =0
dx
1 1
dy 2 dy 2
18 y =8 x y 3
= x 3
dx 3 dx 3
1
2 3
dy 8 x x
= dy 3
dx 18 y =
dx 2 13
y
3
6-23
2 2
xy + x y =1

dy dy
y+x
dx (
+ 2 x y 2+ x 2 2 y )
dx
=0
6-26
3
x y 2 =2 x + y
dy dy
x + 2 x 2 y = y2 x y 2
dx dx
3 1

dy y2 x y 2
=
y 2+ x ( 3 2 dy
2
y
dx
=2+ )
dy
dx
dx x+ 2 x 2 y
1 3
3 dy dy
x y 2 =2 y 2
6-24 2 dx dx
y + y=2 x2
1 3
dy dy dy 2 y 2
+ ( y ) 2 =4 x =
dx dx dx 3 1
x y 2 1
2
1
dy 1 2 dy
+ y =4 x
dx 2 dx 6-27
y
dy 4x x+
=
dx 1
1

1+ y 2
2

6-25
y dy e
y

x+ =
dx ye y

4
6-31
y xy +ln ( xy )=0
x + dy 1 dy
y+x + + y+ x =0
dy 3 dy
dx ( xy ) dx
4 y =4 x 34
dx dx dy dy 1
x + x =y y
y dx dx ( xy )
x +
1
y y
3 dy ( xy )
=
4 x 34 dx x+ x
dy
=
dx
6-32
y 5=x 2 y 3 + x 3 y 2+1
6-28
x 2+3 y 2x =6
dy dy dy
5 y4
dx
=2 x y 3 + x 2 3 y(dx ) (
+ 3 x 2 y 2+ x 3 2 y
dx )
dy
2 x +6 y =0
dx
4 dy 3 2 dy 2 2 3 dy
5y =2 x y +3 x y +3 x y +2 x y
dx dx dx
dy
6y =2 x
dx
dy dy dy
5 y4 3 x 2 y 2 x 3 y =2 x y 3 +3 x 2 y 2
dx dx dx
dy 2 x
=
dx 6 y
dy 2 x y 3 +3 x 2 y 2
= 4
dx 5 y 3 x2 y2 x 3 y
6-29
y e y =x
6-33
dy
y
e +y e
dx ( )
=0y 2 y = y 2x 2
dy dy
2 =2 y 2 x
dx dx
y dy y
ye =e
dx dy dy
2 2 y =2 x
dx dx
dy 2 x ( x+ y )=seny (x y )
=
dx 22 y
dy dy
1+
dx (
=cosy ( x y )+ seny 1
dx )
dy dy
1+ =cosyxcos y 2+ s eny seny
dx dx
dy dy
+ seny =cosyxcos y 2 + seny
dx dx

dy cosyxcos y 2 + seny
=
dx 1+ seny
6-34
xlnx=lny +1
lnx1 1 dy
=
x y dx
1 dy lnx
=
y dx x
lnx
dy x
=
dx 1
y

6-35
( x+ y )
=seny
( x y )
Problemas del 6-36 al 6-45

6-36
1 1
+ =1 en( 2,2)
x y

1 x 1 +1 y1 =1
dy
1 x 2 +1 y2 =0
dx
dy
1 y 2 =1 x2
dx
2
dy 1 x
=
dx 1 y2

dy y 2
=
dx x 2

y 2 22 4
= = =1
x 2 22 4

6-37
y 33 y 2 +3 y=3 ( x+ 1 ) en ( 2,3 )
dy dy dy
3 y2 6 y +3 =3
dx dx dx
dy 3
= 2
dx 3 y 6 y +3

3 3
2
= 2
3 y 6 y+ 3 3 ( 3 ) 6 ( 3 )+ 3
3 3
= =0.25
2718+3 12

638
xy+ x y 4 =12 en ( 9,1 )
1
( xy ) 2 + x y 4 =12
1
1 dy dy
2 dx (
( xy ) 2 + y + x + y 4 + x 4 y 3
dx )
=0

1
dy dy 1
x + 4 x y3 = ( xy ) 2 y y 4
dx dx 2
1
1
( xy ) 2 y y 4
dy 2
=
dx x + 4 x y3
1 1
1 1
( xy ) 2 y y 4 ( 91 ) 2 ( 9 )( 1 ) ( 9 ) ( 1 )4
2 2
= =12
x+ 4 x y3 9+ 4 ( 9 )( 1 )3

6-39
2 2 2 2
x y =x + y en ( 2 , 2 )

dy
2 x y 2+ x2 2 y ( dx )
=2 x+ 2 y

dy
2 x2 y =2 x+2 y2 x y 2
dx

dy 2 x+ 2 y 2 x y 2
=
dx 2 x2 y

2
2 x +2 y 2 x y 2( 2)+2( 2)2( 2)(2)
2
= 2
2x y 2(2) ( 2)

6-40
1 1
x ( 1+ y ) 2 + y (1+ x ) 2 =4 en ( 4,0 )
1 dy 1
x ( 1+ y ) + y ( 1+ x )=0
2 dx 2
1 dy 1
x ( 1+ y ) = y ( 1+ x )
2 dx 2
dy y + yx
=
dx x + xy

y + yx ( 0 ) + ( 0 )( 4 ) 0
= = =0
x + xy ( 4 )+ ( 4 )( 0 ) 4

6-49
y 3 + x+ y+ x 3=20 en (2,3 )
2 dy dy 2
3y +1+ +3 x =0
dx dx

2 dy dy 2
3y + =13 x
dx dx

dy 13 x 2
=
dx 3 y 2 +1

13 ( 2 )2 13
= =0,4
3 ( 3 )2 +1 28

x(2)
y3=0,4
y3=0,4 x0,8
0,4 x + y2,2=0

6-50
5 y 34 y 5=x en (1,1 )
dy dy
15 y 2 20 y 4 =1
dx dx
dy 1
=
dx 15 y 220 y 4

1 1 1
= = =0,2
15 ( 1 ) 20 ( 1 ) 1520 5
2 4

y1=0,2(x1)
y1=0,2 x0,2
0,2+ y0,8=0

6-61
2 2
x + y =10
dy
2 x +2 y =0
dx
dy
2y =2 x
dx
dy 2 x
=
dx 2 y

6-62
2 2
x = y y en ( 2 ,2 )
dy dy
2 x =2 y
dx dx
dy dy
2 y + =2 x
dx dx
dy 2 x
=
dx 2 y+1

2 ( 2 ) 2.8
= =
2 ( 2 )+ 1 3

y-2= (x-1,4)
y-2= x